VD_FINDINFO HC / 2010 / 538 vom 12. Oktober 2010 - VD Tribunal cantonal (2010)
EXPULSION DE LOCATAIRE, LOYER, LOGEMENT, DEMEURE DU DÉBITEUR, RÉSILIATION IMMÉDIATE | 257d CO, 457 al. 1 CPC, 23 LPEBL, 25 LPEBL, 29 LPEBL